Estudo das potencialidades dos resíduos de biomassa da Amazônia Legal para aproveitamento tecnológico, social e ambiental - Romão, Debora Cristina de Freitas (Universidade Federal do Tocantins, 2022)
The Legal Amazon is home to vast biodiversity and, thus, specific and differentiated agroforestry resources on the part of the plant production chain that support traditional communities through diversified and commercial activities. Among these resources, such as lignocellulosic biomasses, which, after processing, are large in proportion of waste. From this information, due to their physicochemical characteristics, it is possible to obtain several compounds of high added value with applicability within the context of biorefineries. The residues of green coconut, babassu and Brazil nut in the husk fraction were studied. These residues were subjected to techniques such as immediate chemical analysis (moisture content, ash, volatile matter, and fixed carbon), Soxhlet extraction, acid hydrolysis, UV spectroscopy, x-ray diffraction, pyrolysis, Brunauer-Emmett-Teller analysis. (BET), analysis by Gas Chromatography Mass Spectrometry (GC‑MS) and calculations to estimate the economic and energy potential seeking to produce compounds such as sugars, bio-oil, biochar, and other value-added bioproducts were studied. The contents of total reducing sugars and lignin were higher than 28% and 30%, respectively. The cellulose crystallinity varied between 25 and 40%, with higher values for babassu, which also presented higher values of glucose and total sugar. The yields found for the biochar and the bio-oil from the green coconut husks were 31% and 30%, respectively. The main components found in bio-oil were furfural (29.23%), phenol (22.18%) and isoeugenol (10.26%), compounds that can be used in the production of fine chemical and plastics, agrochemicals, biomaterials, in the pharmaceutical and food industry. The biochar presented surface area values (BET and Langmuir) greater than 300 m2g-1 and a micropore volume of 0.11 cm3g-1, which can be used as a satisfactory adsorbent. The estimated theoretical energy potential of biochar and bio-oil were 208,107,180 MJ and 190,205,438 MJ, equivalent to 3,729,518.4 tons of coconut husks, that would be enough to supply the energy consumption of 5,734,747 Brazilian homes in a period of 12 months.